KAJIAN PRODUKTIVITAS TENAGA KERJA TEBANG TEBU DI PABRIK GULA MADUKISMO - Rusli, Arraffi Musyaffa; Suswatiningsih, Tri Endar; Trimerani, Resna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The level of productivity is a requirement for determining the parameters of a company's success in facing business competition and increasing company revenue. This study aims to analyze the productivity of the sugarcane cutting workforce and what are the factors that influence the productivity of the sugarcane cutting workforce. The data used is primary data using a questionnaire which is then analyzed using multiple linear regression, then transformed into natural logarithmic form (Ln) which aims to minimize any violations of the assumptions of normality and classical assumptions. In addition to primary data, there is also secondary data taken from existing data in the company. This research was conducted to coincide with the harvest season in September 2022. The average productivity of sugarcane harvesters in a day is 7.59 quintals. The factors that influence the productivity of labor in the sugarcane harvest are the age of the worker, family responsibilities, the area of land that can be harvested and compensation.